Wave Soldering Coupled Thermal-mechanical Simulation of Multi-layer Ceramic Capacitors. Issue 4 (January 2021) - Su, Wei; Luo, Wenhao; Li, Junkui; Liu, Renhuai
Abstract: In this paper, the thermal-mechanical coupling finite element analysis of MLCC wave soldering with heat conduction and heat convection is calculated, and the steady-state temperature field and transient temperature field as well as the stress distribution of MLCC are obtained. Using the finite element analysis method of indirect thermal-mechanical coupling, the stress analysis is carried out with the temperature field as the boundary condition, and the thermal-structural coupling model is established. By analyzing the thermal stress of MLCC, the weak parts sensitive to thermal stress are determined, which provides a useful reference for solving the reliability problem of MLCC wave soldering.